Schistosome TRP channels: An appraisal - Swarna Bais; Robert M. Greenberg (International Journal for Parasitology: Drugs and Drug Resistance, 2020)
Ion channels underlie electrical excitability in cells and are essential for a variety of functions, most notably neuromuscular and sensory activity. They are also validated targets for a preponderance of approved anthelmintic compounds. Transient receptor potential (TRP) channels constitute an ion channel superfamily whose members play important roles in sensory signaling, regulation of ion homeostasis, organellar trafficking, and other key cellular and organismal activities. Unlike most other ion channels, TRP channels are often polymodal, gated by a variety of mechanisms. Furthermore, TRP channels fall into several classes or subtypes based on sequence and structure. Until recently, there had been very little investigation of the properties and functions of TRP channels from parasitic helminths, including schistosomes, but that situation has changed in the past few years. Indeed, it is now clear that at least some schistosome TRP channels exhibit unusual pharmacological properties, and, intriguingly, both a mammalian and a schistosome TRP channel are activated by praziquantel, the current antischistosomal drug of choice. With the latest release of the Schistosoma mansoni genome database, several changes in predicted TRP channel sequences appeared, some of which were significant. This review updates and reassesses the TRP channel repertoire in S. mansoni, examines recent findings regarding these potential therapeutic targets, and provides guideposts for some of the physiological functions that may be mediated by these channels in schistosomes.